The Effectiveness of Spider Diagrams in Improving Descriptive Writing Skills of 7th Grade Students - Seychella Arvian Widya Putri (Retain: Journal of Research in English Language Teaching, 2026)
This study investigated the effectiveness of Spider Diagrams in improving the descriptive writing skills of 7th-grade students at a junior high school in Jombang. Using a quasi-experimental design, 56 students were selected via purposive cluster sampling and divided into an experimental group (taught using Spider Diagrams) and a control group (taught using traditional methods). Students' descriptive writing skills were assessed through pre- and post-tests, evaluated using the Jacob et al. (1981) rubric, which covered content, organization, vocabulary, language use, and mechanics. A Mann-Whitney U test revealed a statistically significant difference (p=0.001) in post-test scores, with the experimental group showing higher improvement. The highest improvements were observed in content (M=27.07) and language use (M=21.17), though the improvement in mechanics (M=3.77) was the lowest. While effective in facilitating writing ideas, Spider Diagrams should be combined with other strategies to ensure comprehensive improvement, particularly in the technical aspects of writing.